A non-equilibrium approach to model flash dynamics with interface transport. (August 2019) - Romo-Hernandez, Aarón; Hudon, Nicolas; Erik Ydstie, B.; Dochain, Denis
Abstract: In this paper, we present a modeling framework for a class of multiphase chemical systems based on non-equilibrium thermodynamics. Compartmental modeling is used to establish the dynamic properties of liquid–vapor systems operating far from thermodynamic equilibrium. In addition to the bulk-phase molar/energetic dynamics, interface transport processes yield to algebraic constraints in the model description. The irreversible system is thus written as a system of differential-algebraic equations (DAEs). The non-equilibrium liquid–vapor DAE system is shown to be of index one. A local stability analysis for the model shows that the equilibrium state is unstable for non-isobaric operation regimes, whereas numerical evidence shows that isobaric operation regimes are stable. To extend the stability analysis, internal entropy production for the irreversible flash-drum is presented as a Lyapunov function candidate.